Relationship between sleep quality and work productivity online motorcycle driver in Makassar City - Sausan, Qonitah; Ibrahim, Hasbi; Syarfaini, Syarfaini (Universitas Islam Negeri Alauddin Makassar, 2025)
Erracting working hours can affect sleep pattern and sleep quality for online motorcycle drivers. This study aimed to determine the relationship between sleep quality and work productivity online motorcycle driver in Makassar city. This research was a quantitative study with cross sectional design with 90 driver for sample. The instrument used are The Pittsburgh Sleep Quality Index (PSQI) and work productivity questionnaire. This study results showed that 88,5% of drivers had poor sleep quality with high work productivity. The results of the Chi-square test shows that there was no significant relationship between sleep quality and work productivity (p=0,107). The test results respondent characteristics (age, gender, last education, marital status, years of work, and type of work) also was no significant relationship with work productivity online motorcycle drivers. Drivers need to manage work time so as not excessive to change sleep pattern and sleep quality.